The Informal City - Selod, Harris; Tobin, Lara (World Bank, Washington, DC, 2018)
This paper proposes a theory of urban land use with endogenous property rights. Socially heterogeneous households compete for where to live in the city and choose the type of property rights they purchase from a land administration which collects fees in inequitable ways. The model generates predictions regarding sorting and spatial patterns of informality consistent with developing country cities. It also highlights non-trivial effects of land administration reforms in the presence of pecuniary externalities, possibly explaining why elites may have an interest in maintaining inequitable land administrations that insulate them from competition for land from the rest of the population.